Inflammatory bowel disease: clinical aspects and treatments - Fakhoury, M.; Negrulj, Rebecca; Mooranian, Armin; Al-Salami, Hani (Dove Medical Press Ltd., 2014)
Inflammatory bowel disease (IBD) is defined as a chronic intestinal inflammation that results from host-microbial interactions in a genetically susceptible individual. IBDs are a group of autoimmune diseases that are characterized by inflammation of both the small and large intestine, in which elements of the digestive system are attacked by the body's own immune system. This inflammatory condition encompasses two major forms, known as Crohn's disease and ulcerative colitis. Patients affected by these diseases experience abdominal symptoms, including diarrhea, abdominal pain, bloody stools, and vomiting. Moreover, defects in intestinal epithelial barrier function have been observed in a number of patients affected by IBD. In this review, we first describe the types and symptoms of IBD and investigate the role that the epithelial barrier plays in the pathophysiology of IBD as well as the major cytokines involved. We then discuss steps used to diagnose this disease and the treatment options available, and finally provide an overview of the recent research that aims to develop new therapies for such chronic disorders.